THE ROLE OF STATE REGULATION IN THE DEVELOPMENT OF THE SECURITIES MARKET - LUTSKEVYCH, Oleksandr (Scientific journal «World of Finance», 2020)
Introduction. The issue of state regulation of the securities market, which is a very necessary and important process for the world economy as a whole and for Ukraine in particular, is investigated. Aim is to study approaches to regulating the domestic securities market and to find ways to improve it. Results. It is substantiated that the mechanism of state regulation of the securities market largely determines the model of state regulation of the entire financial sector of the country. Currently, the problem of regulating the financial market is to establish a relationship between the banking sector and the entire financial market. In this regard, special terms – “mega-regulation” or “cross-sectoral supervision and regulation of the financial market” for integrated supervision of the financial sector have been introduced into the scientific circulation, which consists in the possibility of cross-sectoral, integrated supervision of all sectors of the financial market, developing and applying uniform standards and technologies for the regulation and supervision of different types of financial institutions. It is determined that the domestic securities market is characterized by self-regulation, which, like state regulation, adheres to the goals and principles of activity that are to ensure the stability of the financial market, protect the interests of all financial market participants and reduce the risks of activity. Conclusions. Having studied the basic approaches to the regulation of the securities markets in different countries, we consider it expedient to introduce into the domestic practice of the mega-regulator, since the transition to mega-regulation is the main modern tendency of reforming the financial regulation.